Narrativas de un grupo de jóvenes universitarias sobre el consumo de alcohol. (2023)
This research aims to analyze the different narratives constructed by five young university women regarding alcohol consumption. For this purpose, a qualitative methodology was used and a semi-structured interview was used as a technique. Important aspects such as frequency, spaces of consumption and activities associated with it were found; in the same way, variables such as the main reasons for alcohol intake were recognized, and also within this work it will be seen how the interviewees located moments in which they committed some risky behavior, for being under the influence of alcohol.